The OpenGATE ecosystem for Monte Carlo simulation in medical physics. (21st September 2022) - Sarrut, David; Arbor, Nicolas; Baudier, Thomas; Borys, Damian; Etxebeste, Ane; Fuchs, Hermann; Gajewski, Jan; Grevillot, Loïc; Jan, Sébastien; Kagadis, George C; Kang, Han Gyu; Kirov, Assen; et al.
Abstract: This paper reviews the ecosystem of GATE, an open-source Monte Carlo toolkit for medical physics. Based on the shoulders of Geant4, the principal modules (geometry, physics, scorers) are described with brief descriptions of some key concepts (Volume, Actors, Digitizer). The main source code repositories are detailed together with the automated compilation and tests processes (Continuous Integration). We then described how the OpenGATE collaboration managed the collaborative development of about one hundred developers during almost 20 years. The impact of GATE on medical physics and cancer research is then summarized, and examples of a few key applications are given. Finally, future development perspectives are indicated.